2008
DOI: 10.4054/demres.2008.18.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single parenthood on educational aspiration and student disengagement in Korea

Abstract: The recent rapid increase in divorce, along with its distinctive cultural and welfare environments for single-parent families, makes Korea an interesting case for examining effects of single parenthood on children's education. Using data from Korean 9th and 12th graders, I compare the levels of educational aspiration and student disengagement between students with two parents and those with a single parent, distinguishing divorced single fathers, widowed single fathers, divorced single mothers, and widowed sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…There have been very few studies comparing children in single-parent families and children in 'intact' (two-parent) families in Asia. A recent study by Park (2008) finds that in Korea, children in singleparent families have lower educational aspirations and higher levels of disengagement than children from two-parent families. A more complicated picture is presented by Xu et al's (2007) study of children in single-parent families in China. In comparison to intact families, children in single parent families express lower wellbeing, but this is mediated by academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…There have been very few studies comparing children in single-parent families and children in 'intact' (two-parent) families in Asia. A recent study by Park (2008) finds that in Korea, children in singleparent families have lower educational aspirations and higher levels of disengagement than children from two-parent families. A more complicated picture is presented by Xu et al's (2007) study of children in single-parent families in China. In comparison to intact families, children in single parent families express lower wellbeing, but this is mediated by academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the United States and other Western societies have consistently found educational disadvantages associated with single parenthood, particularly due to divorce (Borgers, Dronkers, & Van Praag, 1996; Kiernan, 1992; McLanahan & Sandefur, 1994). Because the rapid increase in divorce in Korea is very recent, research on relationships between single parenthood and children's education is limited; however, there is some evidence that, as in the United States, single parenthood has a strong negative association with children's educational outcomes in Korea (H. Park 2007a, 2008). This evidence, combined with our results showing that divorce is increasingly concentrated at the lower end of the educational spectrum, points to the potentially important implications of changing family behavior in Korea for social stratification and the reproduction of disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…The husband or the father also shares responsibility with the wife in educating prenatal children by giving the gentle touch to the fetus. In the case when the Husband is dead or incapable of accompanying the pregnant wife for a long time, the woman will probably face mental problems such as feelings of loss, economic, and social issues of [33].…”
Section: The Spiritual and Physical Prenatal Educationmentioning
confidence: 99%